Autonomous navigation of robots for precise location of pollutants in water (2024)
The goal of this study is to develop a state-of-the-art micro-robot navigation system that autonomously detects and navigates heavily contaminated areas in the tank using automatic constant potentiometers, while remotely monitoring biosensors. The integration of a constant potentiometer enables real-time data collection and cyclic voltammetry analysis to determine the presence and concentration of heavy metals in various materials. The constant potentiometer was connected to a microcontroller-based system to facilitate real-time data processing and remote monitoring. The results showed that the constant potentiometer could reliably detect a large number of conductive ions, especially in iron cyanide and wine samples. However, the high power consumption of the constant potentiometer limited the microrobot's ability to navigate and collect data at the same time, highlighting the need for a higher capacity battery to meet the power requirements. The study concludes that while this integration is a breakthrough in environmental monitoring technology, future research should focus on optimizing power management and improving the efficiency of the overall system for simultaneous navigation and data collection. This work demonstrates the potential of autonomous robots to improve water quality monitoring and public health protection.